How social media crisis response and social interaction is helping people recover from Covid-19: an empirical investigation - Bukar, Umar Ali; A. Jabar, Marzanah; Sidi, Fatimah; Nor, R. N. H.; Abdullah, Salfarina; Ishak, Iskandar (Springer, 2022)
Community resilience following a crisis has become essential to avoid panic. In contrast, social media usage has been practical to improve public resilience. However, the impacts of social media crisis response and social interaction have not been fully addressed. Therefore, this study aims to investigate the effects of social media crisis communication on public resilience. The study data were collected through an online medium, and the final responses consist of 393 observations, mainly of Malaysians who have experienced Covid-19 isolation, quarantine, or lockdown. The assessments of the reflective measurement models based on path analysis in PLS-SEM are reliable and valid. The Cronbach’s alpha, rho_A, composite reliability, and discriminant validity revealed acceptable values. PLS prediction algorithm was run to assess the model’s predictive power, and the findings show that the predictive relevance is satisfactory. Furthermore, the IPMA was applied to evaluate the model’s usefulness, which compares the level of the variables from the performance scale mean value against the importance level. The result shows that all the variables are useful and reveal good performance. Thus, crisis management and communication activities should pay more attention to these variables for effective social media crisis communication. Thus, the study offers theoretical and practical implications in the field of social media-based crisis communication and crisis informatics.